2003
DOI: 10.1525/sp.2003.50.4.550
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Unwanted Pets: A Case Study in How Institutions "Think" about Clients' Needs

Abstract: The research on organizational framing and the metaphor of institutional "thinking" highlight the ways that social problems organizations shape the ameliorative services they deliver. Social problems work then perpetuates representations of problems that may not match the conditions clients face. This study extends social problems literature to argue that organizations sometimes "think" differently about the problems they intend to solve than do persons involved with these problems in everyday life. Using ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 31 publications
0
53
0
2
Order By: Relevance
“…Other US studies support this suggestion:57.2% of owners had more than one reason, and up to five separate reasons for relinquishment of pet cats to 12 U.S. animal shelters (Salman, New et al 1998. It has been proposed that some owners surrender cats for behavioural reasons, but report a different reason because they believe the animal will have a better chance of being re-homed , DiGiacomo, Arluke et al 1998, Irvine 2003. Another factor which might have contributed to the low number of people reporting behavioural problems as a reason for surrender is that many people surrendering a pet experience feelings of guilt (Shore 2005), and attributing the reason to something beyond their control, such as accommodation issues, might help deflect blame from the relinquisher and from the pet (Shore, Petersen et al 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other US studies support this suggestion:57.2% of owners had more than one reason, and up to five separate reasons for relinquishment of pet cats to 12 U.S. animal shelters (Salman, New et al 1998. It has been proposed that some owners surrender cats for behavioural reasons, but report a different reason because they believe the animal will have a better chance of being re-homed , DiGiacomo, Arluke et al 1998, Irvine 2003. Another factor which might have contributed to the low number of people reporting behavioural problems as a reason for surrender is that many people surrendering a pet experience feelings of guilt (Shore 2005), and attributing the reason to something beyond their control, such as accommodation issues, might help deflect blame from the relinquisher and from the pet (Shore, Petersen et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Research investigating pet owner's decisions to surrender a cat to a shelter found that the reasons can be multifaceted and, in fact, many owners have several reasons contributing to the final decision (DiGiacomo, Arluke et al 1998) (Salman, New et al 1998). Further to this, there is evidence suggesting that people will avoid giving surrender reasons that may be perceived to influence the rehomability of the pet , Irvine 2003. For example, the reason for the surrender of the cat may be due to an undesirable behavioural trait; however, if the owner believes that this may contribute to the cat being euthanased, they may choose to report a reason not related to the animal itself .…”
Section: Seasonal Admission Patternsmentioning
confidence: 99%
“…It is at this point within the timeline that Irvine (2003) situates the construction of the problem of pet overpopulation and the development of organizations and institutions to deal with the problem. Prior to the Civil War, the concept of a "homeless" pet didn't exist.…”
Section: History Of Pet Keeping and Animal Shelteringmentioning
confidence: 99%
“…As these animals held little economic value for any owner, fewer animals were retrieved and the pound master killed the majority (Miller 2007). The fear of the scourge of rabies carried by roaming dogs in urban areas caused large scale round ups of homeless dogs who were euthanized by pound masters (Irvine 2003). In 1866, Henry Bergh founded The American Society for the Prevention of Cruelty to Animals (ASPCA) partially in response to perceived abuses by the local pound master.…”
Section: History Of Pet Keeping and Animal Shelteringmentioning
confidence: 99%
See 1 more Smart Citation